Pre and Post–Merger Financial Performance Analysis of Commercial Banks in Nepal (The International Research Journal of Management Science, 2023)
Purpose: This study attempts to examine the effect of merger on the financial performance of Nepalese commercial banks.Methodology: This paper employs a descriptive and causal comparative research design to examine the financial performance of commercial banks involved in six merger deals as of mid-July 2022, with a sample of four merger deals completed before mid-July 2018. Mean, standard deviation, paired sample t-test, Pearson correlation, regression analysis, and the VIF test, are utilized for data analysis. Financial performance is evaluated using nine key ratios (EPS, NWPS, P/E ratio, CD ratio, CAR, NPL ratio, ROA, ROE, and NPM). Secondary data covering six years (2010 to 2019), excluding the specific merging year, are analyzed.Findings: The analysis of pre- and post-merger financial performance in the sample commercial banks revealed statistically significant differences in EPS, NWPS, ROA, and NPM. Positive correlations were observed between the pre- and post-merger periods for EPS, NWPS, CD ratio, CAR, NPL ratio, ROA, ROE, and NPM, excluding the P/E ratio. The merger proved beneficial for Nepalese commercial banks, leading to improved profitability in terms of EPS, ROA, and NPM in the post-merger phase. However, factors like CD ratio, CAR, and NPL ratio, regulated by the NRB, showed no significant changes post-merger. Although banks experienced increased P/E ratio and ROE, the impact was deemed insignificant. Notably, CAR had the most significant impact on both pre- and post-merger ROA.Implication: The results derived from the study are relevant to managers for future merger decisions and can be used for the selection of a suitable partner for future merger activities.Value: It contributes to a better understanding of the overall merger scenario in Nepalese banking sector, as well as the relationship between certain restrictions and merger.